Phenolic Substances, Flavor Compounds, and Textural Properties of Three Native Romanian Wine Grape Varieties. Issue 1 (2nd January 2016) - Urcan, Delia Elena; Lung, Mihai-Lucian; Giacosa, Simone; Torchio, Fabrizio; Ferrandino, Alessandra; Vincenzi, Simone; Río Segade, Susana; Pop, Nastasia; Rolle, Luca
Abstract : In this work, the chemical compositions and texture characteristics of three native Romanian wine grape varieties (Fetească regală, Fetească alba, and Fetească neagră) were studied. We assessed the distinct characteristics directly linked to their phenolic compositions, volatile profiles, and mechanical properties and compared these characteristics with those of Pinot noir grapes. The effect of the growing zone was also evaluated. Various spectrophotometric indices directly related to the phenolic compositions of berry skins and seeds were determined. The detailed phenolic compositions (anthocyanins, hydroxycinnamoyl tartaric acids, and stilbenes) of the skins were determined using high-performance liquid chromatography methods. Free and bound volatile compounds in the berries were quantified by gas chromatography/mass spectrometry. The textural properties of the skins and seeds were measured by instrumental texture analysis. The results showed high diversity among the varieties and zones that affected the enological potential. Among the white varieties, Fetească albă grapes could be less susceptible to browning as a consequence of their lower trans -caffeoyltartaric acid concentration, whereas Fetească regală grapes from Cluj had the highest concentrations of total free and bound volatile compounds, particularly terpenes and norisoprenoids. Among the red varieties, Fetească neagră was identified as a promising variety to be exploited in the future for its particular phenolic characteristics, particularly those grapes grown in Mica. Nevertheless, Fetească neagră grapes grown in Cluj had the highest total glycosidically bound terpene concentrations. Finally, differences in the mechanical and/or acoustic properties of the skins and seeds could strongly influence the kinetics and completeness of phenolic compound extractions.